2015
DOI: 10.1590/1982-021620151753515
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre os achados do teste masking level difference e do reflexo acústico em crianças com transtorno fonológico

Abstract: Resumo: OBJETIVO: investigar os achados do teste Masking Level Difference com os resultados do reflexo acústico e a composição do sistema fonológico de crianças com transtorno fonológico, com o propósito de verificar se há associações que possam auxiliar a compreensão do processo de aquisição de linguagem atípica. MÉTODOS: estudo quantitativo, observacional e descritivo, desenvolvido por meio de levantamento secundário de um banco de dados, constituído de avaliações fonoaudiológicas de 110 crianças com trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(15 reference statements)
1
6
1
Order By: Relevance
“…The abovementioned researchers who used MLD in students with speech-language (12) disorder, found greater occurrence of such disorder on the male gender, and a greater percentage of altered individuals in the test, however, as in the current study, there was no significant difference to the 5 to 10 year old age ranges. The authors explain that this majority result may have occurred due to the great number of children who showed otitis media during childhood, which may have brought consequences to the hearing skills.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The abovementioned researchers who used MLD in students with speech-language (12) disorder, found greater occurrence of such disorder on the male gender, and a greater percentage of altered individuals in the test, however, as in the current study, there was no significant difference to the 5 to 10 year old age ranges. The authors explain that this majority result may have occurred due to the great number of children who showed otitis media during childhood, which may have brought consequences to the hearing skills.…”
Section: Discussioncontrasting
confidence: 70%
“…Nevertheless, the study that evaluated the MDL in Australian kids showed a predominance of males (11) and, although the age average is similar to the one shown in this study (9.4 years old) and had no difference between the genders, the MDL value was superior, as previously referenced (11.21dB). Another study, yet Brazilian, also showed a male prevalence (73.7%) in the sample and did not show difference in the rest result, compared to female, in an age range of 5 to 10 years (12) old. Yet, there was no presentation of an acquired value average, considering that they were distributed into normal and altered in face of a normality used for the test, which was of 9dB.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For the Masking Level Difference (MLD) test (Table 1), we observed that the Musicians group had a higher average than the Non-musicians group. The test involves auditory binaural integration and, as described in the literature, studies with MLD in children have shown that the peripheral and brainstem auditory processes responsible for MLD are completely formed by the sixth month of life [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Exactly 4 of the 6 studies included typical normal developing children in the control group [12,[19][20][21]. In contrast, the remaining two studies [22,23] had no control group. All selected studies utilised behavioral APD tests to assess temporal processing, binaural interaction, integration, and auditory closure.…”
Section: General Features Of the Selected Articlesmentioning
confidence: 99%